Enhancing metal solubility and phytoextraction in soil under Indian mustard - Rahul Mishra; SP Datta; Mahesh C Meena; BS Dwivedi (Journal of Oilseed Brassica, 2026)
In phyto-extraction slow removal rate of metals by plant is the main constraint in the way of making effective use of thisgreen technique in managing contaminated site. Hence, an attempt has been made to study the effect of selected organicand inorganic amendments on enhancing efficacy of phytoextraction of Zn, Cd and Pb in contaminated soil using Indianmustard (Brassica juncea cv. Pusa Vijay) as a test crop. Results indicated that Cd availability in soil was increased from38.7 to 96.7% under different amendments, whereas Pb availability enhanced from 53.8 to 94.0%. All the amendmentsenhanced the EDTA and DTPA-extractable Zn, Cd and Pb in soil. Cadmium removal by shoot of mustard was enhancedto the extent of 125, 62.5, 175, 175 and 212% under green manure, EDTA, S+S oxidizing bacteria, metal solubilizingbacteria and green manure + metal solubilizing bacteria treated soil, respectively over control. Root parameters (i.e. rootlength, diameter, surface area) also improved under different amendments. Application of green manure and metalsolubilizing bacteria was the most efficient in enhancing the Zn, Cd and Pb removal by Indian mustard and phytoextractionfrom practical point of view.